Device with rectangular section for layer-by-layer snow sampling - M. P. Tentyukov (Лëд и снег, 2015)
A new snow layer probing device with a rectangular section is described in the paper. This device allows receiving snow samples with the undisturbed structures of snow layers, and more accurately reflects the actual value of the snow water equivalent. Application of a new snow probing device in snow measurements provides a new way to organize the monitoring dynamics of snow density layer variability, to estimate density of certain snow types in the snow cover, including the total or vertically averaged one, and to visualize the features of the snow stratigraphy structure. Snow layer probing device with a rectangular section as opposed to the cylindrical weight snow devices has constructive advantages. It also can be used in the calibration weight snow measurement devices that will ensure the comparability of the snow shooting results made in different climatic zones.